2012
DOI: 10.1016/j.jenvman.2012.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Environmental consequences of processing manure to produce mineral fertilizer and bio-energy

Abstract: Liquid animal manure and its management contributes to environmental problems such as, global warming, acidification, and eutrophication. To address these environmental issues and their related costs manure processing technologies were developed. The objective here was to assess the environmental consequences of a new manure processing technology that separates manure into a solid and liquid fraction and de-waters the liquid fraction by means of reverse osmosis. This results in a liquid mineral concentrate use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 16 publications
(26 reference statements)
1
81
1
2
Order By: Relevance
“…Moreover, biogas production involves the production of a valuable co-product such as digestate, a stream rich in nutrients which could be used as an organic fertilizer for crop cultivation in substitution of mineral fertilizers (De Vries et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, biogas production involves the production of a valuable co-product such as digestate, a stream rich in nutrients which could be used as an organic fertilizer for crop cultivation in substitution of mineral fertilizers (De Vries et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This methodology has been widely used to assess the environmental profile of bioenergy production systems and numerous studies can be found in the literature (Dressler et al, 2012;Hartmann, 2006;Jury et al, 2010;Lansche and Müller, 2012). In these studies, bioenergy systems provide good opportunities to achieve environmental benefits when fossil fuels are replaced or when they are compared with conventional waste management (Börjesson and Berglund, 2007;De Vries et al, 2012). However, it is interesting to highlight that the environmental performance of a bioenergy system from biogas is considerably affected by the feedstock considered, the final use of the biogas and the digestate management (Poeschl et al, 2012a;b).…”
Section: Introductionmentioning
confidence: 99%
“…During the conversion of biomass by anaerobic digestion into biogas, methane (CH4), carbon dioxide (CO2), and trace gases (e.g. hydrogen gas) are produced, which can be used to produce bio-energy in the form of electricity, heat, or transport fuel (Hamelin et al, 2011;De Vries et al, 2012a). The remaining product after digestion is called 'digestate' and can be used as organic fertilizer replacing artificial fertilizer (Börjesson and Berglund, 2007).…”
Section: Case 1: Wheat Middlingsmentioning
confidence: 99%
“…79% natural gas-based and 21% light fuel oil-based in the Netherlands. The rest is used for digestion processes and, therefore, no alternative products were included (De Vries et al, 2012a). The digestate that is transported and applied to the field as fertilizer was assumed to be substituted by marginal mineral N, P, and K fertilizer.…”
Section: Case 1: Wheat Middlingsmentioning
confidence: 99%
See 1 more Smart Citation